Adjuvant imatinib for high-risk GI stromal tumor: analysis of a randomized trial - Joensuu, Heikki; Hohenberger, Peter (Journal of clinical oncology, 2016)
PurposeThree years of adjuvant imatinib therapy are recommended for patients with GI stromal tumor (GIST) with high-risk features, according to survival findings in the Scandinavian Sarcoma Group XVIII/AIO (Arbeitsgemeinschaft Internistische Onkologie) trial. To investigate whether the survival benefits have persisted, we performed the second planned analysis of the trial.Patients and MethodsEligible patients had macroscopically completely excised, KIT-positive GIST with a high risk of recurrence, as determined by using the modified National Institutes of Health criteria. After surgery, the patients were randomly assigned to receive imatinib for either 1 or 3 years. The primary objective was recurrence-free survival (RFS), and the secondary objectives included survival.ResultsA total of 400 patients were entered onto this open-label study between February 4, 2004, and September 29, 2008. During a median follow-up of 90 months, 171 recurrences and 69 deaths were detected. Patients assigned to the 3-year group had longer RFS than those assigned to the 1- year group; 5-year RFS was 71.1% versus 52.3%, respectively (hazard ratio [HR], 0.60; 95% CI 0.44 to 0.81; P < .001), and survival was 91.9% versus 85.3% (HR, 0.60; 95% CI, 0.37 to 0.97; P = .036). Patients in the 3-year group survived longer in the subset with centrally confirmed GIST and without macroscopic metastases at study entry (93.4% v 86.8%; HR, 0.53; 95% CI, 0.30 to 0.93; P = .024). Similar numbers of cardiac events and second cancers were recorded in the groups.ConclusionThree years of adjuvant imatinib therapy results in longer survival than 1 year of imatinib. High 5-year survival rates are achievable in patient populations with high-risk GIST.